2015
DOI: 10.1038/leu.2015.330
|View full text |Cite
|
Sign up to set email alerts
|

Similar clinical features in follicular lymphomas with and without breaks in the BCL2 locus

Abstract: Approximately 15% of follicular lymphomas (FLs) lack breaks in the BCL2 locus. The aim of this study was to better define molecular and clinical features of BCL2-breakpoint/t(14;18)-negative FLs. We studied the presence of BCL2, BCL6 and MYC breaks by fluorescence in situ hybridization and the expression of BCL2, MUM1, CD10, P53 and Ki67 in large clinical trial cohorts of 540 advanced-stage FL cases and 116 early-stage disease FL patients treated with chemotherapy regimens and radiation, respectively. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 27 publications
7
41
2
Order By: Relevance
“…The presence of lymphoma cells carrying a MBR, mcr or a minor BCL2 rearrangement in the PB and/or BM was determined by qualitative PCR in the majority of patients (71·6%), who were defined as stage I/II FL according to the conventional staging procedures, including a negative BM histology. This figure is somewhat higher than what expected (Leich et al , ), but it should be underlined that 6 cases (9%) were identified by the analysis of minor and newly defined BCL2 rearrangements, whilst the proportion of MBR+ and mcr+ cases (63%) is comparable with the one (66%) reported in our original experience (Pulsoni et al , ), confirming the limits of the standard staging procedures.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The presence of lymphoma cells carrying a MBR, mcr or a minor BCL2 rearrangement in the PB and/or BM was determined by qualitative PCR in the majority of patients (71·6%), who were defined as stage I/II FL according to the conventional staging procedures, including a negative BM histology. This figure is somewhat higher than what expected (Leich et al , ), but it should be underlined that 6 cases (9%) were identified by the analysis of minor and newly defined BCL2 rearrangements, whilst the proportion of MBR+ and mcr+ cases (63%) is comparable with the one (66%) reported in our original experience (Pulsoni et al , ), confirming the limits of the standard staging procedures.…”
Section: Discussionsupporting
confidence: 76%
“…In order to understand the pathogenesis of early stage FL, we certainly recognize the value of better characterizing early stage FL without t(14;18) compared to those with t(14;18). Leich et al () reported that, at variance from advanced FL, about 50% of early stage FL cases do not show a t(14;18) in the LN by fluorescence in situ hybridisation (FISH), but the over‐expression of the BCL2 protein is still present in 69% of them. The molecular mechanisms underlying these cases certainly need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MYC/BCL6-DH DLBCL are highly heterogeneous in their molecular subtypes, indicating their diverse COO, notwithstanding the high prevalence of NOTCH2 mutations [23,24]. BCL6 translocation is recurrently seen in both follicular and marginal zone lymphoma [56][57][58][59]. It would be interesting to explore whether MYC/BCL6-DH DLBCL also result from high-grade transformation of a low-grade lesion such as follicular or marginal zone B-cell lymphoma or their precursor lesions, and their heterogeneous molecular subtypes reflect their inherent features from their derived low-grade lesion.…”
Section: Discussionmentioning
confidence: 99%
“…MYC translocations can also be found in transformed or high‐grade follicular lymphoma (FL) (Pasqualucci et al , ), indicating a more aggressive phenotype with adverse prognosis, similar to the aforementioned DHL (Koch et al , ). However, in a recent study including high‐ and low grade FL, MYC breaks were also found in 6·3% of low‐grade FL, but the fraction of cells affected by this alteration was low compared to high‐grade FL with MYC translocations (Leich et al , ). These data reflect the complexity in the continuum of transformation of FL into a more aggressive disease, where the role of MYC activation is not fully understood.…”
Section: Role Of Myc In the Pathobiology Of Haematological Malignanciesmentioning
confidence: 96%